FEMS microbes. - Federation of European Microbiological Societies (Oxford : Oxford University Press, 2020)
FEMS Microbes is an open access journal covering all aspects of microbiology and the microbial world around us. The journal aims to publish high quality basic and applied research within diverse areas of microbiology, as well as current methodological advancements that are of general interest to a wide audience.
Description based on online resource; title from home page (viewed on April 2, 2020).
Keywords: Microorganisms -- Periodicals